Survival and fermentation activity of probiotic bacteria and oxidative stability of omega-3 oil in co-microcapsules during storage. (May 2016) - Eratte, Divya; Wang, Bo; Dowling, Kim; Barrow, Colin J.; Adhikari, Benu
Highlights: L. casei and tuna oil were effectively co-microencapsulated in WPI–GA complex coacervate. Synergism between vitality and oxidative stability was observed, when co-microencapsulated. Vitality of L. casei and oxidative stability of tuna oil decreased with storage. Spray dried co-microcapsules were more stable than individual microcapsules on storage. Freeze dried co-microcapsules were less stable than individual microcapsules on storage. Abstract: Tuna oil (O) and probiotic bacteria Lactobacillus casei (P) were co-microencapsulated in whey protein isolate (WPI)–gum Arabic (GA) complex coacervate. The co-microcapsules (WPI-P-O-GA), L. casei microcapsules (WPI-P-GA) and tuna oil microcapsules (WPI-O-GA) were converted into powder using spray and freeze drying. The interaction between probiotic bacteria and omega-3 oil in co-microcapsules, particularly in terms of oxidative stability of omega-3 oil and vitality/viability of probiotic bacteria and any synergistic outcome, was studied. The effect of storage temperature (5 and 25 °C) and time (90 days) on the survival and fermentation activity of L. casei and oxidative stability of tuna oil in the microcapsules/co-microcapsules was determined. A synergism between oxidative stability of omega-3 oil and vitality of probiotic bacteria was observed, when they were co-microencapsulated and spray dried. These co-microcapsules will likely have utility in functional food formulations due to simple and cost effective stabilisation and delivery of two important functional ingredients.